2015
DOI: 10.2196/resprot.4032
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Phone and Web-Based Intervention for Improving Mental Well-Being in Young People With Type 1 Diabetes: Design of a Randomized Controlled Trial

Abstract: BackgroundYoung people with type 1 diabetes experience elevated levels of emotional distress that impact negatively on their diabetes self-care, quality of life, and disease-related morbidity and mortality. While the need is great and clinically significant, a range of structural (eg, service availability), psychological (eg, perceived stigma), and practical (eg, time and lifestyle) barriers mean that a majority of young people do not access the support they need to manage the emotional and behavioral challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…We found 2009 citations using the search strategy run between May and August 2016, from which we identified 30 abstracts as potentially relevant. The authors of six trials were contacted for additional information (Aubin 2014;Blackwell 2012;Cheng 2013;Clarke 2015;Ketchen 2006;Quittner 2013). One author reported that their trial had been prematurely discontinued due to lack of funding (Quittner 2013).…”
Section: Results Of the Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 2009 citations using the search strategy run between May and August 2016, from which we identified 30 abstracts as potentially relevant. The authors of six trials were contacted for additional information (Aubin 2014;Blackwell 2012;Cheng 2013;Clarke 2015;Ketchen 2006;Quittner 2013). One author reported that their trial had been prematurely discontinued due to lack of funding (Quittner 2013).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…These included a trial of iACT, an interactive mHealth monitoring system to enhance psychotherapy for adolescents with sickle cell disease (Cheng 2013), a pilot randomised trial of a cognitive behavioural treatment for insomnia and depression in adolescents Clarke 2015, and a trial of U-care, an internet-based self-help programme of psychosocial support and psychological treatment (Mattson 2013). Although an ANZCTR report stated that one trial had been stopped early, no reply was received from the author when we contacted them for confirmation (Clarke 2015). Two further study protocols were identified during an update of the search in August 2017.…”
Section: Ongoing Studiesmentioning
confidence: 99%
“…Based on statistical power of 0.8 and probability level of P <.05, a sample size of 26 per group (that is, 52 for each of the two groups) will be needed for one-tailed tests. Given the expected attrition rate of up to 50% [ 81 ], our target total sample size is therefore 104 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes-specific cognitive behavioral group therapy for people with diabetes and subclinical depression [34] and webbased guided CBT for people with T1DM or T2DM and mild to moderate depression [35] have also reported significant reductions in both depression and diabetes distress. Further trials utilizing Internet and mobile technologies for the mental health of people with diabetes are currently being conducted [36], including our own study using a local iCBT study for depression in people with diabetes [37]. A recent report of an online diabetes self-management program, of the sort which could compliment depression resources reported 'small but significant' benefits as a stand-alone program [38] but points to the need for a mixture of face-to-face and online resources targeted to individual needs.…”
Section: Discussionmentioning
confidence: 99%